Prevalence of surgical site infection post caesarean with increased patient load during COVID-19 pandemic in tertiary care centre - Raut, Prashansa Santosh; Wani, Reena; Shetty, Theertha; Khade, Roshni; Mulchandani, Anjali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Increased referrals and workload during the pandemic lead to overcrowding in hospitals and increase in LSCS rates. Surgical site infection is one of the most common complication post LSCS causing physical and mental duress to the patients. The objective of the study was to analyse the effect of COVID-19 on SSI, the incidence, commonly associated factors and bacteriology of SSI. The design was prospective study design. Methods: 577 patients undergoing LSCS were studied from Day 1 till 30 days post LSCS from 1st August 2020 to 31st October 2020. Results: Out of 577, 28 (4.85%) patients developed SSI. 60% of SSI in our study were unbooked, 50% had haemoglobin less than 9.9 g/dl. Most common risk factor for developing of SSI included pre-eclampsia (32.14%) followed by previous LSCS (28.57%). Common organism isolate was MRSA (25%) and 75% required surgical management. Conclusions: Regular ANC visits can help in managing comorbidities at an earlier stage leading to reduction in SSI. Strict aseptic precautions should be followed to reduce SSI in cases with PROM and second stage arrest. SSI rate is not influenced by COVID-19 status but hospital facilities and overcrowding definitely have an effect.